DevOps dashboard - Bruno, Francisco João Lúcio (2022)
DevOps stands for development and operations. DevOps is a culture that empowers both development and operations teams to reduce time to market, make incremental improvements in response to changing conditions, and create a more efficient development process. Software development and delivery is a very complex practice, and managing it is even harder. Any kind of system or process needs to gather data and metrics to understand how it is performing. Understandably, measuring is essential in creating valuable software. However, measuring software is not easy and has been a problem for several organizations. There is the notion of utilizing a dashboard to ease the way DevOps teams interact and respond to data collected from systems to aid stakholders measure and monitor. The Design Science Research (DSR) methodology was chosen to build an artefact – the DevOps dashboard - and evaluate its value to the DevOps community. Several versions of the artifact were developed as part of an improvement process, with each iteration validated through interviews. It was identified that the dashboards generally accessible in the DevOps community are extremely specialized and lack a broader perspective of the entire ecosystem to help stakeholders in decision-making. The contribution of this research is the developed dashboard that allows more significant monitoring of a DevOps system employing metric categories that follow visualization best practices to improve user experience and impact the user decision process positively.